Practice and Principles of Blended Learning in ESL Pedagogy: Strategies and Techniques - Alam, Sohaib (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Blended learning combines the traditional face to face classroom experiences with new innovative learning technologies that have the potential to democratize language learning. It is supported by an intelligent adaptive technology and it enables to learn the learners as the learner learns. Adaptive learning technologies are the way through which it learns the learners as the learner wants to learn not as the teachers want to teach. It also understands the different level of understanding of the students and provides the materials accordingly. The concept of blended learning can be defined as using a computer and online materials and sources as a tool for learning and not necessarily learning about computers or online materials. A model of teaching that combines or merges classroom learning and online learning where the instruction of the lessons follow with organized teacher interaction; and, the discussion in the classroom with students and computing devices. The main focus of the study is to provide support system to the students in the classroom teaching. Blended learning offers flipping a classroom between face to face teaching and web based or online teaching. This paper aims to provide the idea of blending the language teaching in ESL classroom. It also explores the ways through which one can flip their classroom and incorporate blended learning in language pedagogy.